2019
DOI: 10.1051/e3sconf/20199212004
|View full text |Cite
|
Sign up to set email alerts
|

Vane shear strength of bio-improved sand reinforced with natural fibre

Abstract: In the recent developments, bio-improvement has considerably enhanced the geotechnical properties and reduced degradation of loose desert sand without the environmental concerns. However, the effect of bio-improvement on sand weakens due to water submergence. Therefore, it is necessary to explore the techniques for retaining the strength of bio-improved sand in water submerged state. So, this paper reports the geotechnical performance of submerged bio-improved sand reinforced by discrete natural fibres. The de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Date palm fibers along with xanthan gum were used to enhance dune sand. Results showed that fiber increased the vane shear strength of the treated sand at a low concentration of xanthan, while high xanthan contents (2%) experienced almost the same strength with and without adding fiber [175]. The addition of sheep wool along with sodium alginate showed significant growth in the compressive strength performance of cohesive soil from 2.23 MPa for natural soil to 4.44 MPa for reinforced biotreated soil.…”
Section: Effect Of Adding Fibermentioning
confidence: 95%
See 1 more Smart Citation
“…Date palm fibers along with xanthan gum were used to enhance dune sand. Results showed that fiber increased the vane shear strength of the treated sand at a low concentration of xanthan, while high xanthan contents (2%) experienced almost the same strength with and without adding fiber [175]. The addition of sheep wool along with sodium alginate showed significant growth in the compressive strength performance of cohesive soil from 2.23 MPa for natural soil to 4.44 MPa for reinforced biotreated soil.…”
Section: Effect Of Adding Fibermentioning
confidence: 95%
“…For sand treated by xanthan gum, it has been reported that the MDD and OMC behaviors were symmetrical such that 1% biopolymer caused the highest MDD and lowest OMC to be reached, then by increasing the biopolymer content, MDD reduced and OMC started to increase. The initial growth in MDD was due to the lubrication effect of biopolymer until 1%, while for higher content, xanthan showed a negative effect so that a swelling behavior of the treated soil was observed [151,175]. The xanthan-treated clay showed different behavior in comparison to the biomodified sand.…”
Section: Compaction Testmentioning
confidence: 98%
“…The purpose of the current study is to develop a suitable methodology to apply the EICP technique to improve dune sand in Oman. Other ongoing eco-friendly practices include using biopolymers such as xanthan gum [17][18][19][20] to improve the strength and durability of dune sand. For the current study, the literature review revealed that the microbial technique is slower and needs a longer duration if we compare microbial and chemical cementation.…”
Section: Introductionmentioning
confidence: 99%
“…The unconfined compressive strength increases with sediment contentment up to 75% and then decreases with the increase in sediment content. Also, to further develop the dune sand properties there were different added substances have been utilized; such as the use of marble waste [9], biopolymer and fibres [10], sediments [8], cement and dust [11], and fly ash [12].…”
Section: Introductionmentioning
confidence: 99%